1998
DOI: 10.1046/j.1423-0410.1998.7410007.x
|View full text |Cite
|
Sign up to set email alerts
|

How to Stabilize the Level of lonized Calcium and Citrate during Plateletpheresis

Abstract: With this stepdown citrate reduction protocol, we obtained a significant reduction of injected citrate without the complication of platelet clumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…[ 27 ] Other studies also reported that although, the fall in tCa ++ and tMg ++ were modest and not significant, the drop in iCa and iMg was statistically significant ( P < 0.001). [ 1 25 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Other studies also reported that although, the fall in tCa ++ and tMg ++ were modest and not significant, the drop in iCa and iMg was statistically significant ( P < 0.001). [ 1 25 28 ]…”
Section: Discussionmentioning
confidence: 99%